Biomimetic hydrogel by enzymatic crosslinking of pullulan grafted with ferulic acid. (15th December 2020) - Hadrich, Ahdi; Dulong, Virginie; Rihouey, Christophe; Labat, Béatrice; Picton, Luc; Le Cerf, Didier
Graphical abstract: Highlights: Ferulic acid (FA) was grafted on pullulan (PUL) using N, N '-carbonyldiimidazole. An associative behaviour was observed in dilute solution. The antioxidant properties provided by FA are preserved. Action of laccase resulted in the formation of a cytocompatible hydrogel. The initial PUL concentration and the amount of grafted FA controlled the properties. Abstract: A novel eco-friendly two-step synthesis process of neutral pullulan (PUL)-ferulic acid (FA) conjugates was reported in this work. Ferulic acid was first transformed to activated ferulate-imidazolide using N, N '-carbonyldiimidazole (CDI), a green activated reagent. Issued product was then reacted with pullulan. PUL-FA derivatives were characterized by FTIR and 1 H NMR leading to substitution degrees (DS) between 0.02 and 0.1 (mol FA per mol PUL repeat unit). The study in dilute regime indicated an associative behavior with the presence of aggregate structures in solution due to the hydrophobic interactions between the grafted FA onto polysaccharide backbones. Laccase from Trametes versicolor was then used to crosslink polysaccharide chains to obtain biomimetic PUL-FA hydrogels. Gelling's kinetics were analyzed with rheology in dynamic mode showing the impact of laccase amount, DS and concentration. Mechanical and swelling properties appear related only to DS and concentration of PUL-FA products.